New nomenclatural combinations for taxa of Pentanema (Asteraceae) occurring in Ukraine - Boiko, G.V.; Korniyenko, O.M.; Mosyakin, S.L. (Український ботанічний журнал, 2018)
Recent molecular phylogenetic results demonstrated that the genus Inula in its traditional circumscription is
polyphyletic and its type, I. helenium, belongs to a clade phylogenetically distant from the clade containing the majority of
species earlier placed in Inula. The nomenclatural proposal to conserve the generic name Inula with I. hirta as the conserved type
has not been adopted. Because of that the genus Inula s. str. now comprises ca. 5 species (I. helenium and its relatives). The genus
Pentanema was considerably re-circumscribed to include most of taxa earlier treated in Inula. Several taxa of Inula s.l. occurring
in Ukraine, however, did not have respective names available in Pentanema, but such names are needed for the forthcoming
checklist of vascular plants of Ukraine (in preparation). The following new nomenclatural combinations are validated:
Pentanema asperum (Poir.) G.V.Boiko & Korniyenko, comb. nov. (Inula aspera Poir.), P. caspicum (F.K.Blum) G.V.Boiko,
Korniyenko & Mosyakin, comb. nov. (I. caspica F.K.Blum in Ledeb.), P. × medium (M.Bieb.) G.V.Boiko & Korniyenko, comb.
nov. (I. media M.Bieb.), and P. sabuletorum (Czern. ex Lavrenko) G.V.Boiko & Korniyenko, comb. nov. (I. sabuletorum Czern.
ex Lavrenko). Additionally, two new subspecies-rank combinations, P. salicinum (L.) D. Gut.Larr. et al. subsp. asperum (Poir.)
Mosyakin and P. salicinum subsp. sabuletorum (Czern. ex Lavrenko) Mosyakin, comb. nov., are proposed by the third author. Результати недавніх молекулярно-філогенетичних досліджень показали, що род Inula у традиційному розумінні є поліфілетичним, а його тип, I. helenium, належить до клади, що філогенетично віддалена від клади, що містить більшість видів, які раніше включалися до Inula. Номенклатурна пропозиція законсервувати родову назву Inula із законсервованим типом I. hirta не була прийнята. Через це род Inula тепер включає приблизно 5 видів (I. helenium та споріднені види). Обсяг роду Pentanema був значно змінений, завдяки чому до нього зараз включено більшість таксонів, що раніше розглядалися у складі Inula. Проте, декілька таксонів Inula s. l., які поширені в Україні, не мали відповідних назв у роді Pentanema, але такі назви є необхідними для запланованого нового видання номенклатурного конспекту судинних рослин України. Здійснені такі нові номенклатурні комбінації: Pentanema asperum (Poir.) G.V.Boiko & Korniyenko, comb. nov. (Inula aspera Poir.), P. caspicum (F.K.Blum) G.V.Boiko, Korniyenko & Mosyakin, comb. nov. (I. caspica F.K.Blum in Ledeb.), P. × medium (M.Bieb.) G.V.Boiko & Korniyenko, comb. nov. (I. media M.Bieb.), P. sabuletorum (Czern. ex Lavrenko) G.V.Boiko & Korniyenko, comb. nov. (I. sabuletorum Czern. ex Lavrenko). Крім того, дві нові комбінації у ранзі підвиду запропоновані одним з авторів: P. salicinum (L.) D. Gut.Larr. et al. subsp. asperum (Poir.) Mosyakin, comb. nov. та P. salicinum subsp. sabuletorum (Czern. ex Lavrenko) Mosyakin, comb. nov. Результаты недавних молекулярно-филогенетических исследований показали, что род Inula в традиционном понимании является полифилетическим, а его тип, I. helenium, относится к кладе, филогенетически удаленной от клады, включающей большинство видов, ранее относимых к Inula. Номенклатурное предложение законсервировать родовое название Inula с законсервированным типом I. hirta не было принято. Поэтому род Inula теперь включает лишь около 5 видов (I. helenium и родственные виды). Объем рода Pentanema был значительно пересмотрен, вследствие чего в этот род сейчас включено большинство таксонов, ранее рассматриваемых в составе Inula. Однако несколько распространенных в Украине таксонов Inula s.l. не имели соответствующих названий в роде Pentanema, но такие названия необходимы для планируемого нового издания номенклатурного конспекта сосудистых растений Украины. Осуществлены следующие новые номенклатурные комбинации: Pentanema asperum (Poir.) G.V.Boiko & Korniyenko, comb. nov. (Inula aspera Poir.), P. caspicum (F.K.Blum) G.V.Boiko, Korniyenko & Mosyakin, comb. nov. (I. caspica F.K.Blum in Ledeb.), P. × medium (M.Bieb.) G.V.Boiko & Korniyenko, comb. nov. (I. media M.Bieb.), P. sabuletorum (Czern. ex Lavrenko) G.V.Boiko & Korniyenko, comb. nov. (I. sabuletorum Czern. ex Lavrenko). Кроме того, одним из авторов предложены две новые комбинации в ранге подвида: P. salicinum (L.) D.Gut.Larr. et al. subsp. asperum (Poir.) Mosyakin, comb. nov. и P. salicinum subsp. sabuletorum (Czern. ex Lavrenko) Mosyakin, comb. nov.